Credible Research Designs for Minimum Wage Studies - Sylvia Allegretto; Arindrajit Dube; Michael Reich; Ben Zipperer (Institute for the Study of Labor (IZA), 2013)
We assess alternative research designs for minimum wage studies. States in the U.S. with larger minimum wage increases differ from others in business cycle severity, increased inequality and polarization, political economy, and regional distribution. The resulting time-varying heterogeneity biases the canonical two-way fixed effects estimator. We consider alternatives including border discontinuity designs, dynamic panel data models, and the synthetic control estimator. Results from four datasets and six approaches all suggest employment effects are small. Covariates are more similar in neighboring counties, and the synthetic control estimator assigns greater weights to nearby donors. These findings also support using local area controls.
Keywords: J08; J23; J38; J42; J63; J64; 330; minimum wage; youth employment; border discontinuity; policy evaluation